(untitled) (Journal of Economic Research & Business Administration, 2018)
The article reveals the role and importance of zakat in the tax system of Islamic states as an instrument of social support for low-income strata of the population. The mechanism of collecting zakat is considered: objects, subjects, tax base and calculation mechanism. Zakat is one of the tools to reduce and eliminate poverty. Zakat is an absolute gain, both from the point of view of the individual and from the point of view of society. Benefits socially low-income groups and the payer of zakat (in the religious sense). This article contains useful information for future researchers in the field of Islamic finance, specifically Zakat. Subject. Zakat as a special tax in the Islamic tax system governing social inequality. Goals. To analysis of the principles of operation and mechanism of charging zakat. To show the role of Zakat as the main tax in the Islamic tax system. The results of the study showed that the problem of the functioning of the Zakat is one of the most debated problems of economists by economists not only from Muslim countries, but also from other countries. Application area. The results of the study can be used in the introduction of Islamic experience in the regulation of social inequality, into the tax system of other countries. Also with the economic cooperation of the countries of the Islamic world.